Financial difficulties in the social companies of Bogota (2013)
In this 2013 has highlighted the existing problems in the State Social Enterprises Bogota for lack of resources for the provision of health services; of twenty fourteen are at high risk, a situation that has been presented from the same implementation of Law 100 allows financial intermediation and introduced the figure of Social Enterprise of State should work with its own assets, administrative autonomy and the ability to generate their own resources for their financial sustainability, causing them to have to compete with private entities which sell health services at lower costs and have modern equipment and infrastructure, a situation that can’t offer these for lack of budget and staff resources to modernize the equipment of this network and to provide better quality services to the population demands.